Pengembangan UMKM Kelanting Delima Melalui Media Digital dan Teknologi Informasi Untuk Meningkatkan Kualitas Pemasaran - Firmansyah; Meizary, Ary; Amnah (Jurnal Pengabdian Masyarakat Tapis Berseri (JPMTB), 2025)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the Indonesian economy, including in preserving traditional culinary. One of the MSMEs engaged in regional specialties is Kelanting Delima. However, in the digital era, the main challenges faced by this MSME are limitations in marketing and low utilization of digital technology. The method of implementing activities includes socialization, training, and assistance in the use of social media, marketplaces, and strengthening product branding. The results of this program show an increase in business actors' understanding of digital marketing, the use of social media as a promotional tool, and success in opening online stores on various marketplace platforms. In addition, the design of product packaging and logos has also been updated to be more attractive and professional. The implementation of this digital strategy has a positive impact on increasing the number of customers and expanding the market which is no longer limited to the local area. Overall, this service aims to increase the competitiveness and market reach of Kelanting Delima MSMEs through the application of digital media and information technology in marketing strategies, so that it becomes an effective solution in improving the quality of marketing and competitiveness of Kelanting Delima MSMEs.